Time Discounting and Wealth Inequality - Epper, Thomas; Fehr, Ernst; Fehr-Duda, Helga; Kreiner, Claus Thustrup; Lassen, David Dreyer; Leth-Petersen, Søren; Rasmussen, Gregers Nytoft (American Economic Review, 2020)
This paper documents a large association between individuals’ time discounting in incentivized experiments and their positions in the real-life wealth distribution derived from Danish high-quality administrative data for a large sample of middle-aged individuals. The association is stable over time, exists through the wealth distribution and remains large after controlling for education, income profile, school grades, initial wealth, parental wealth, credit constraints, demographics, risk preferences, and additional behavioral parameters. Our results suggest that savings behavior is a driver of the observed association between patience and wealth inequality as predicted by standard savings theory. (JEL C91, D15, D31, E21)